2020
DOI: 10.3390/ijms21103677
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Regulates Source to Sink Metabolic Homeostasis and Promotes Growth of Rice Plants under Sulfur Deficiency

Abstract: Being an essential macroelement, sulfur (S) is pivotal for plant growth and development, and acute deficiency in this element leads to yield penalty. Since the last decade, strong evidence has reported the regulatory function of silicon (Si) in mitigating plant nutrient deficiency due to its significant diverse benefits on plant growth. However, the role of Si application in alleviating the negative impact of S deficiency is still obscure. In the present study, an attempt was undertaken to decipher the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 82 publications
2
18
0
Order By: Relevance
“…(d) Metabolite and hormonal profiling; metabolites and hormones are both vital for regulation of plant nutrition homeostasis. During the last few years, our research studies provided some evidence in this regard, indicating the impact of Si nutrition under K [ 49 ], S [ 54 , 55 ] and Mg [ 29 ] deficiencies. Moreover, the role of Si in metabolic changes under arsenic [ 98 ] as well as the change in amino acid levels in rice has been previously reported [ 99 ].…”
Section: Remark and Prospectivementioning
confidence: 85%
See 1 more Smart Citation
“…(d) Metabolite and hormonal profiling; metabolites and hormones are both vital for regulation of plant nutrition homeostasis. During the last few years, our research studies provided some evidence in this regard, indicating the impact of Si nutrition under K [ 49 ], S [ 54 , 55 ] and Mg [ 29 ] deficiencies. Moreover, the role of Si in metabolic changes under arsenic [ 98 ] as well as the change in amino acid levels in rice has been previously reported [ 99 ].…”
Section: Remark and Prospectivementioning
confidence: 85%
“…We have shown that, in barley plants subjected to osmotic stress and S deficiency simultaneously, Si modulated the genes involved in S and ABA homeostasis. Even though another stress trigger (osmotic stress) combined with S deficiency, nevertheless, this pioneering work could open the new windows to study deeply the cross talk between Si and S. Therefore, in our recent work, we attempted to decipher the role of Si application solely on the metabolism of Si-accumulator rice plants under S deficiency [ 55 ]. The study demonstrated a distinct source to sink metabolic regulation coupled with changes in the expression level of S and Si transporters leading to a consequent higher accumulation of Si and lower accumulation of stress phytohormones in the shoots, therefore maintaining plant growth and development under S deprivation [ 49 ].…”
Section: Si and Macro-nutrient Deficiencymentioning
confidence: 99%
“…Work on interactions of Si with sulfur (S) is at a preliminary stage. Early results indicate that uptake and accumulation of S was unaffected by Si supply in forages crops ( Panicum maximum and Brachiaria ruziziensis × Brachiaria brizantha ) ( Buchelt et al, 2020 ) while Si supply even decreased shoot accumulation of S in barley and rice exposed to S deficiency ( Maillard et al, 2018 ; Réthoré et al, 2020 ). Molecular analysis also showed that the addition of Si tended to decrease transcript levels of S transporters (OsSULTR) in rice ( Réthoré et al, 2020 ; see Table 1 ).…”
Section: Interactions Of Silicon With Macronutrientsmentioning
confidence: 99%
“…Analysis of N was realized using an elemental FLASH 2000 CHNS analyzer (Thermo Fisher Scientific, Waltham, MA, United States) according to the instructions of the manufacturer from 2.5 mg of homogenized and lyophilized plant material. NH 4 + , NO 3 , and sulfate (SO 4 2– ) were extracted and analyzed according to Réthoré et al (2020) using high pressure ion chromatography with a conductivity detector (Dionex ICS5000 +, Thermo Fisher Scientific, Villebon-sur- Yvette, France).…”
Section: Methodsmentioning
confidence: 99%